Cranial reconstruction with prefabricated 3D implant after a gunshot injury – A case report - Malivuković, Ana; Novaković, Nenad; Lepić, Milan; Minić, Ljubodrag; Stepić, Nenad; Djordjević, Boban; Rasulić, Lukas (Vojnosanitetski pregled, 2017)
Introduction. Complex defects of skull bones with different etiology, still present the challenge in reconstructive surgery. The goldstandard for cranioplasty is the autologous calvarial bone graft removed during surgery which cannot be always applied, especially in gunshot wounds for sometimes complete bone destruction. Autologous reconstruction with split calvarial, rib bones or iliac bone graft is also possible. Materials routinely used for reconstructions like titanium mesh, polymethyl metacrylate (PMMA), and other have numerous disadvantages and limitations. Case report. We presented a patient with gunshot injury to the head with residual large bone defect in the frontal region, with involvement of the skull base, and open frontal sinus. After conservative treatment, six months after the injury, reconstruction of the residual bone defect was performed. The chosen material was computer-designed PEEK-OPTIMA® implant, manufactured on the basis of MSCT scan. This material has not been used in this region so far. The postoperative and follow-up period of the next 12 months passed without surgical complications, neurological deficit, with satisfactory functional and aesthetic results. Conclusion. Implanted bone replacement was designed and manufactured precisely according to the skull defect, and we found it suitable for the treatment of complex defects of the cranium. Early results are in favor of this cranioplasty method over standardized materials. Therefore, this material is expected to become a method of choice for reconstructive surgery of bony defects of the face and skull especially in complex cases.